Massive Intradural Dermoid Cyst Without Sinus Tract. Issue 7 (October 2017) - Abouhassan, William; Chao, John An Kuang; Lehman, James A.
Abstract : Abstract: Dermoid cysts can present as a rare, benign, congenital intracranial tumor of neuroectoderm origin trapped during embryogenesis. Past clinical reports have reported lesions in the posterior fossa, at the midline, and in the intradural region all in conjunction with a superficial sinus tract. The authors present a unique patient of a completely intracranial, intradural, dermoid tumor of the midline cerebellum devoid of any evidence of sinus tract. The histological characteristics, radiological features, and management of this unusual patient are described.